Ewolucja społecznej odpowiedzialności biznesu w Polsce - Jastrzębska, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The purpose of this article is to show the evolution of the idea of corporate social responsibility in Poland. It is based on a critical analysis of literature, web research and participatory observation. Both birth of the idea of corporate social responsibility and stages of evolution of the way it is understood were similar in Poland and in Western Europe. However, those processes in Poland were delayed and their scale was smaller. The importance of the concept of CSR is also not as rigid and tends to change. This is due to the fact that the concept itself is derived from practice, evolving in response to the needs of society and business. However, the essence of responsibility remains constant and up-to-date.